Interaksi Sosial dalam Lingkungan Panti Asuhan Muhammadiyyah Cingkariang - Luthvita Crishanti Sausan; Fadilla Yusri (Universitas 45 Surabaya, 2024)
A The environment around the orphanage or home environment is the number two environment for changing the character of students, while in an orphanage it is what makes them a family, many people say that children in an orphanage are children of the community without exception, so good forms of social interaction are needed to foster and instilling high values of caring and the value of good communication with people outside the orphanage and inside the orphanage, there are quite a lot of problems that arise and are spoken about by the local community regarding the lack of interaction between orphanage children and their surroundings as well as the orphanage's own family, both from administrators who don't understand the character of the orphanage children, poverty interact with each other and the orphanage staff.